Which are the risks of artificial fertilization? - Di Pietro, Maria Luisa; Minacori, Roberta (Medicina e Morale, 1998)
The article identifies the risks that, either because of the physician's lack of skill, or because of the procedures involved in the human fertilization technique, cause the morbidity and mortality of the woman and/or unborn child. One of the risks for the woman is related to the ovarian stimulation that takes place with a pharmacological induction and that provokes the socalled "ovarian hyperstimulation" and tumors of the breast and ovary. Other risks are related to the complications of the artificial fertilization procedures and these mainly concern the phase of recuperating the oocytes, the "in vitro" culture, and the transfer of the gametes and embryos into the woman's reproductive tract. The oocytes are drawn under ultrasound control with the risk of pelvic or abdominal pain, infection and hemorrhage, whereas the transfer of gametes is carried out through laparoscopy with complications related to the anesthesia. The first risk for the embryo is that it may not reach autonomous life because it is not transferred to the woman's reproductive tract, it did not attach to the uterus, there may be a spontaneous or a provoked abortion, and there is also an increased incidence of perinatal morbidity and mortality. Other negative factors are caused by the micromanipulation of the gametes. Moreover, from an analysis of the literature, it can be seen that those born from artificial fertilization have more congenital malformations and a higher incidence of prematurity. Finally, the inadequate information provided to the couples who turn to artificial fertilization regarding the risks, side effects and percentages of success is together with all these problems.